PENGARUH KOMPETENSI PROFESIONAL GURU PENDIDIKAN AGAMA KRISTEN (PAK) TERHADAP HASIL BELAJAR SISWA - Munte, Bangun (Jurnal Dinamika Pendidikan, 2016)
ABSTRACTThe purpose of this study was to determine how far the effect of professional competenceof Religion teacher towards learning outcomes of the studentsâ cognitive. Due to the timeand effort constraint, Private High School YP.PELITA Pematangsiantar is then chosen asthee location to conduct this study. The population and the sample is 46 students. Themethod used is descriptive, while analysis and tools used in data collection was aquestionnaire enclosed a questionnaire for the variable X (Influence of Religion Teachersof Professional Competence), and to strengthen the collection of such data, do experimentsin the field. To know the effect of the PAK Teacher Professional Competence LearningOutcomes Cognitive Students used a statistical test of correlation coefficient, from thecalculation results obtained by testing the correlation r = 0.45 and a test of determinationas much as 20.25%, while to determine the significance of the correlation coefficientwhether or not to use the real level 0, 05 by using the t test with the testing criteria whent_hit <t_tab then the hypothesis is rejected and unacceptable in other respects. Results oftesting the hypothesis obtained t_hit> t_tab (2.39> 1.68), thus the hypothesis is accepted.The influence of Religion Teachers Professional Competence reached an average of 2.39with a level of classification is very influential, while the Cognitive Learning OutcomesStudents achieving an average of 2.42 with a good classification. So it can be argued thatthe influence of Religion Teachers Professional competence against Cognitive LearningOutcomes of Students in Private School YP.PELITA Pematangsiantar.Keywords: Professional Competence, Cognitive Learning OutcomesABSTRAKTujuan penelitian ini adalah untuk mengetahui sejauhmana pengaruh kompetensiprofesional Guru PAK terhadap Hasil Belajar Kognitif Siswa (Di SMA Swasta YP.PELITAPematangsiantar). Adapaun alasan memilih tempat karena untuk menghemat waktu dantenaga, maka untuk populasi dan sampel penelitian adalah berjumlah 46 Siswa. Metodeyg digunakan adalah deskriptif, sedangkan analisis dan alat yang digunakan dalampengumpulan data adalah angket tertutup berupa kuesioner untuk variabel X (PengaruhKompetensi Profesional Guru PAK ), dan untuk memperkuat pengumpulan data tersebut,dilakukan eksperimen di lapangan. Untuk mengetahui Pengaruh Kompetensi ProfesionalGuru PAK terhadap Hasil Belajar Kognitif Siswa digunakan uji statistik koefisien korelasi,dari hasil perhitungan pengujian korelasi diperoleh r = 0,45 dan uji determinasi sebanyak20,25%, sedangkan untuk mengetahui signifikansi tidaknya koefisien korelasi digunakantaraf nyata 0,05 dengan mengunakan uji âtâ dengan kriteria pengujian bila ð¡âðð¡< ð¡ð¡ððmaka hipotesa ditolak dan dalam hal lain dapat diterima. Hasil pengujian hipotesadiperoleh ð¡âðð¡> ð¡ð¡ðð(2,39 >1,68), dengan demikian hipotesa diterima. PengaruhKompetensi Profesional Guru PAK mencapai rata-rata 2,39 dengan tingkat klasifikasisangat berpengaruh, sedangkan Hasil Belajar Kognitif Siswa mencapai rata- rata 2,42dengan klasifikasi baik. Jadi dapat dikemukakan bahwa adanya pengaruh kompetensiProfesional Guru PAK terhadap Hasil Belajar Kognitif Siswa di SMA Swasta YP.PELITAPematangsiantar.Kata Kunci: Kompetensi Profesional, Hasil Belajar Kognitif